Assessment of Cyfluthrin commercial formulation on growth, photosynthesis and catalase activity of green algae - Sáenz, María Elena (2012)
Aquatic environments of the pampasic region of Argentina are severely affected by agricultural contamination due to an increase in a glyphosate tolerant transgenic variety of soybean crops. The present study is aimed to determine the effects of a commonly used Cyfluthrin commercial formulation (CCF) on growth, some physiological and biochemical parameter of four species of green algae. Significant inhibition of algal growth was observed from 0.1 mg Cyf/l. 96 h IC50 were between 0.92 and 4.85 mg Cyf/l. CCF caused algicidal effects. Photosynthesis was stimulated by 50% in Scenedesmus quadricauda cultures exposed to the lowest concentration (hormesis). Algal photosynthesis inhibition was observed at higher concentrations with IC50 values between 1.7 and 8.9 mg Cyf/l. Similar toxicity endpoints were found as a consequence of applying the traditional methodology of short-term chronic toxicity test of 96 h of exposition and the methodology developed using the Clark type photosynthetic oxygen evolution method. CAT activity was significantly increased between 23% and 33% considering the four species, at a lower concentration than those affecting algal growth and photosynthesis, indicating a potential biomarker. Taking into account that the extent of the soybean crops in the region is about fourteen million hectares, the improvement and extension of environmental tools for early detection of the action of pesticides on this essential group of organisms are discussed.